2014
DOI: 10.5941/myco.2014.42.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Root Rot and Vascular Wilt Diseases in Roselle (Hibiscus sabdariffa L.) in Upper Egypt

Abstract: Roselle (Hibiscus sabdariffa L.) family Malvaceae is an important crop used in food, cosmetics and pharmaceutics industries. Roselle is cultivated mainly in Upper Egypt (Qena and Aswan governorates) producing 94% of total production. Root rot disease of roselle is one of the most important diseases that attack both seedlings and adult plants causing serious losses in crop productivity and quality. The main objective of the present study is to identify and characterize pathogens associated with root rot and wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 9 publications
2
16
0
1
Order By: Relevance
“…Results of this study are in agreement with those reported by (Hassan et al, 2014 andBoulanger et al, 1984).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Results of this study are in agreement with those reported by (Hassan et al, 2014 andBoulanger et al, 1984).…”
Section: Resultssupporting
confidence: 94%
“…According to Ploetz (2000) among the species of Fusarium oxysporum, there are pathogenic and nonpathogenic isolates that cannot be distinguished morphologically. Fusarium oxysporum, F. solani and M. phaseolina are the causal pathogens of wilt and root rot diseases in roselle (Hibiscus sabdariffa L.), endanger roselle production wherever this crop is cultivated extensively (Hassan et al, 2014). Boulanger et al (1984) found that F. oxysporum causes infection to the young plants of H. sabdariffa, the pathogens can damage the crop.…”
Section: Introductionmentioning
confidence: 99%
“…In Qena governorate, the total planted area is around 1,150 ha 45.83 which either recently reclaimed area 966 ha or the old soil of the valley 189 ha . About 1,353 tons out of 2,648 tons 51.1 of the total production of dry yield of roselle are produced by Qena governorate 11 . The amounts of roselle seeds produced that do not use for recultivation process are lacking economic value 12 .…”
Section: Introductionmentioning
confidence: 99%
“…vasinfectum causing wilt in cotton [31]. Fusarium species as pathogens could result in wilt disease in Pisum sativum and roselle plants, with damping-off and root rot wilt diseases [32,33]. Moreover, recent findings indicated F. oxysporum caused root and crown rot on sweet cherry (Prunus avium) in British Columbia.…”
Section: Discussionmentioning
confidence: 99%